The correlation between self-esteem, university commitment and academic performance among undergraduate students at the final year of their degree - Kharsah, Wael Sahdo (2017)
Factors that affect students‘ academic performance are not limited to university lecturers, staff, peers, activities and the syllabus. Demographic factors such as family background, as well as students‘ self-esteem and university commitment affect academic performance. Thus it is very important to reveal how students‘ self-esteem and students‘ university commitment are related to students‘ academic performance. The appreciation of oneself or the lack of it, and commitment can show observable signs that could help learners to improve themselves to achieve better performance. The specific objectives of the study sought to 1- determine the relationship between self-esteem and academic performance among undergraduate students at the final year of their degree at Universiti Malaysia Pahang, 2- determine the relationship between university commitment and academic performance among undergraduate students at the final year of their degree at Universiti Malaysia Pahang, 3- determine the relationship between self-esteem and university commitment among undergraduate students at the final year of their degree at Universiti Malaysia Pahang. To achieve these three objectives, the study used the quantitative method. Participants for this study were 387 undergraduate students from Universiti Malaysia Pahang at the final year of their degree. The selected variable of self-esteem was measured using the Rosenberg Self-Esteem Scale (RSES), while university commitment was measured by using Brittany Davis‘s Scale (2014), which was derived from Allen and Meyer‘s Model (1990), and students‘ academic performance was measured by the university students‘ grade point average (GPA). The variables investigated in this research were chosen through Maslow‘s Theory of Needs (1954). Data was gathered using questionnaires which measured their self-esteem, university commitment, and academic performance. The scores for the level of self-esteem was obtained based on the positive items method rather than the negative items method, as well as the reliability of the Rosenberg Self-Esteem Scale improvement. The results showed: positive, significant relationships were found between self-esteem and academic performance, as well as between self-esteem and students‘ university commitment. By contrast, there was no significant relationship between students‘ university commitment and academic performance. In order to analyse the data, the Pearson Correlation Coefficient and Multiple Regression Analysis were utilised. The results from the Pearson Correlation Coefficient showed a significant relationship between self-esteem and academic performance, but no correlation between university commitment and academic performance. Furthermore, the Multiple Regression Analysis revealed that the component of self-esteem was found to be able to predict the level of academic performance, while the component of university commitment was not found to be able to predict the level of academic performance of the students